A brief measure of social media self-control failure. (July 2018) - Du, Jie; van Koningsbruggen, Guido M.; Kerkhof, Peter
Abstract: People often fail in controlling their social media use when it conflicts with other goals and obligations. To facilitate research on understanding social media self-control failures, we constructed a brief social media self-control failure (SMSCF)-scale to assess how often social media users give in to social media temptations. Social media users ( N  = 405) completed a survey (including a 4-week follow-up) to test the scale's psychometric properties. The self-report SMSCF-scale showed good internal consistency and test-retest reliability. Demonstrating its construct validity, the SMSCF-scale was moderately related to existing problematic media use and general self-control scales. Demonstrating its predictive validity, the SMSCF-scale was positively related to social media use and feelings of guilt about one's social media use and was negatively related to psychological wellbeing. The SMSCF-scale provides a useful indicator of social media self-control failure that could facilitate future research on the psychological processes underlying social media self-control failures. Graphical abstract: Image Highlights: People frequently fail in resisting temptations to use social media. We constructed a short (3-item) scale to assess social media self-control failure (SMSCF). A two-wave survey shows that the SMSCF-scale has good reliability. The SMSCF-scale can be distinguished from other scales assessing problematic social media use. The SMSCF-scale is a useful indicator of everyday social media self-control failure.